Introduction to Embedded System Design Using Field Programmable Gate Arrays - Dubey, Rahul (Springer London : Imprint: Springer, 2009)
As the uses of digital systems continue to proliferate in quantity and variety, field programmable gate arrays (FPGAs) are taking centre-stage in their design. Introduction to Embedded System Design Using Field Programmable Gate Arrays provides a starting point for the use of FPGAs in the design of embedded systems. The text considers a hypothetical robot controller as an embedded application and weaves around it related concepts of FPGA-based digital design. The book details: • use of FPGA vis-à-vis general purpose processor and microcontroller; • design using Verilog hardware description language; • digital design synthesis using Verilog and Xilinx® SpartanTM 3 FPGA; • FPGA-based embedded processors and peripherals; • overview of serial data communications and signal conditioning using FPGA; • FPGA-based motor drive controllers; and • prototyping digital systems using FPGA. The book is a good introductory text for FPGA-based design. It will be useful for both students and designers who have worked with microprocessors and microcontrollers and now wish to move to design using FPGA. Its end-of-chapter exercises and frequent use of example can be used for teaching or for self-study.